Study on the Interaction between Changes in the Quality of Public Sports Services and Multi-Regulation - Gou, Wenjing (International Journal of Social Sciences and Public Administration, 2024)
This study takes the public perception perspective as an entry point to explore the evolution, problems and optimization strategies of public sports service quality. Through literature research, key indicators such as public satisfaction, changes in demand and participation in public sports services are analyzed, and it is found that although the quality of public sports services has improved in recent years, there are still problems such as insufficient matching of supply and demand, lagging behind in the updating of facilities, and uneven service levels. Aiming at these problems, this study proposes a series of optimization strategies and measures, including improving the construction of venues and facilities, expanding service contents, and optimizing the management system. In turn, the public sports service system is constructed and optimized to enhance the public sports experience, meet diversified sports needs, and promote the sustainable and healthy development of national fitness.